ANHYDROUS PARTIAL MELTING EXPERIMENTS ON MORB-LIKE ECLOGITE: PHASE RELATIONS, PHASE COMPOSITIONS AND MINERAL-MELT PARTITIONING OF MAJOR ELEMENTS AT 2-3 GPA - Pertermann M.; Hirschmann M.M. (My University, 2003)
We present melt and mineral compositions from nominally anhydrous partial melting experiments at 2-3 GPa on a quartz eclogite composition (G2) similar to average oceanic crust. Near-solidus partial melts at 3GPa, determined with melt traps of vitreous carbon spheres, have 55-57 wt % SiO2, rather less silica than the dacitic compositions that are generally assumed for near-solidus eclogite partial melts. At 2 GPa, equivalent near-solidus partial melts are less silicic (less than or equal to52 wt % SiO2). The 3GPa near-solidus partial melts (up to meltfractions of -3%) are saturated in rutile and have 5.7-6.7 wt % TiO2. The G2 composition is K2O-poor (0.03 wt%), but a modified composition with 0.26 wt% K2O (G2K) produces dacitic near-solidus melts with 61-64 wt % SiO2. Rutile saturation for G2K extends to higher melt fraction (similar to13%) and occurs at lower TiO2 melt contents (3.3 wt %) than for G2. These results can be understood in terms of a simplified thermodynamic model in which alkalis increase the SiO2 content of liquids saturated in quartz, which in turn diminishes the TiO2 concentrations required to maintain ruble saturation. Additionally, the mode of residual garnet and generation of silicic liquids by partial melting of anhydrous eclogite are linked, as garnet is required to mass-balance formation of appreciable SiO2-rich melt. Partitioning of Na between clinopyroxene and melt shows significant increases with pressure, but ono modest shifts with changing temperature. In contrast, partitioning of Ti between cpx and melt, as well as between cpx and garnet, shows pronounced dependence on temperature for compositions relevant to anhydrous partial melting of eclogite. Mixtures between partial melts of eclogite and primitive picritic Hawaiian magmas are similar to magnesian, SiO2-rich compositions inferred from melt inclusions from the Koolau volcano. However, in detail, no eclogitic partial melt has been identified that is capable of explaining all of the composttional features of the exotic Koolau component. Based on phase compositions in our experiments, the calculated density of near-solidus eclogite is 3440 kg/m(3), notably less than commonly assumed. Therefore, the excess temperature required for a plume to support a given proportion of eclogite in the upper mantle may be less than previously assumed.